Recent Advances in MOF‐Derived Single Atom Catalysts for Electrochemical Applications - Song, Zhongxin; Zhang, Lei; Doyle‐Davis, Kieran; Fu, Xianzhu; Luo, Jing‐Li; Sun, Xueliang (Advanced energy materials, 2020)
Electrocatalysis plays a critical role in clean energy conversion, enabling great improvement for future sustainable technologies. Single atom catalysts (SACs) derived from metal–organic framework (MOF) are emerging extraordinary materials in electrochemical catalytic applications. Covering the merits of unique electronic structure, low‐coordination environment, quantum size effect, and metal–support interaction, SACs promise enhanced electrocatalytic activity, stability, and selectivity in the field of clean energy conversion. In this article, MOF synthesis routes to afford well‐dispersed SACs along with the respective synthesis mechanism are systematically reviewed first, and typical examples of each strategy are carefully discussed. Then the characterization techniques in understanding the isolated and spatial distribution, local electronic structure, coordination environment for SACs, and insights into stable mechanisms provided by density functional theory (DFT) calculations are summarized. In addition, several important electrocatalytic applications and electrocatalytic mechanisms of the MOF‐derived SACs, including for the oxygen reduction reaction, CO2 reduction reaction, nitrogen reduction reaction, hydrogen evolution reaction, oxygen evolution reaction, etc., are highlighted. To facilitate the future development of high‐performing SACs, several technical challenges and corresponding research directions are proposed. This review presents recent progress in the design and synthesis of metal–organic framework (MOF)‐derived single atom electrocatalysts, the ex situ and in situ characterizations, and their remarkable catalytic performance in electrochemical conversion reactions.